PENGGUNAAN SELULOSA MIKROBIAL DARI NATA DE CASSAVA DAN SABUT KELAPA SEBAGAI PENSUBSTITUSI SELULOSA KAYU DALAM PEMBUATAN KERTAS - Khaswar Syamsu, Renny Pespitasari dan Han Roliadi (E-Jurnal Agro-Industri Indonesia) (E-jurnal Agro-Industri Indonesia, 2012)
ABSTRACT Currently, the majority of the world’s pulp and paper is manufactured from raw materials, either wood from industrial forest plantations or natural forests. The rate deforestation in Indonesia increases by 2% per year. The study was conducted to combine microbial cellulose of nata de cassava and coconut husk to reduce the use of wood cellulose in manufacturing pulp and paper. Two factors of experiment are the addition of additives and a combination of microbial cellulose and pulp of coconut husk (100:0, 75:25, 50:50 and 25:75). The yields of microbial cellulose and of coconut-husk pulp were consecutively (dry basis) 80.03% and 39.72%. Physical and strength properties of paper varied, i.e. water content (7.22-10.46%), grammage/basis weight (53.72-68.56 g/m2), tensile index (0.003-0.029 kNm/g), tear index (2.58-16.59 mNm2/g), brightness (8.15-35.1%), printing opacity (45.99-97.08%), and Cobb size60 (46.79-168.17 g/m2 for the smooth/upper surface; and 28.22-183.92 g/m2 for the rough/lower surface). The result of the analysis assuming the conversion of biomass to paper made with 50% pulp of nata de cassava and 50% pulp of coconut husk indicated that the expansion of production of 200 ha can substitute 8,808,356.438 trees per year. With the ammount of this saving trees, 1,233,169.901ton CO2 from the air can be absorbed each year. Keywords: Nata de cassava, coconut fiber, paper, biomass conversion analysis